SIMULASI SISTEM KONTROL OPERASI ON GRID SERTA ISLANDING PEMBANGKIT LISTRIK TENAGA SURYA DI JURUSAN TEKNIK ELEKTRO UNIVERSITAS UDAYANA - Sutawan, Pande K. B.; Kumara, I Nyoman Satya; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i02p11)
An on-grid solar power plant will distribute electric power to the grid in normal conditions. But when the supply of grid outages (islanding), on-grid solar power plant also can’t operate because the loss of the reference signal that is used as a reference for the inverter in the synchronization process. So there is potential loss of power when solar power plant can be used as a substitute source of electrical energy while PLN can’t serve consumers. In this r esearch developed a simulation model that refers to the off grid solar power plant 500 Wp in the Department of Electrical Engineering, University of Udayana and can operate on-grid and off grid when islanding in matlab simulink. In this model made operation scenario where solar power plant operates on grid at the beginning of the simulation and after that operate off-grid (not connected to the grid and supply the local load). The simulation results show the model off grid solar power plant has been able to generate a voltage of 220 V and a frequency of 50 Hz in accordance with the solar power plant at the research site. The simulation results also show model of on grid solar power plant has been able to synchronize to the low voltage grid of PLN not loaded and loaded. On/off grid solar power plant model can operate on-grid or off-grid that corresponds to the operation scenario and produce the same output. Thus solar power plant can supply.
Keywords: PLTS on grid, PLTS off grid, Sinkronisasi.